Development of online learning modules to improve lecturers' digital literacy skills and teaching creativity - Sastra Wijaya; Rifda Cita Zulviah; Fadlilah Fahmi; Teti Trisnawati; Anna Maria Oktaviani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This research is motivated by low levels of digital literacy and limited creativity in teaching among lecturers, as well as the significant obstacles encountered in online learning at the Faculty of Teacher Training and Education, Universitas Primagraha. The purpose of this study is to analyze the needs, develop, and test the feasibility and effectiveness of a Digital Literacy E-Module for lecturers. Using the Research and Development (R&D) method within the ADDIE model, this study involved the entire population of FKIP lecturers, with 36 respondents selected through purposive sampling. Data collection techniques included observation, questionnaires, and tests, using instruments such as expert validation sheets, user response questionnaires, and learning outcome test questions. The results indicated that the E-Module is categorized as